Sensitivity of the CFD mesh for a single rising bubble in a hallimond tube - Azmi, A. (2013)
This paper presents how a single rising bubble experiment in the Hallimond Tube (HT) can be predicted using a computational fluid dynamics model (CFD). The study is emphasized on the effect of CFD Mesh to the pressure coefficient and axial velocity around the bubble. A rigid sphere with the radius of 0.00575 m using flow velocity of 0.0067 m/s was considered in this study. Experimental and simulated data obtained by other researchers in the similar study were used to validate the simulation results from the computational fluid dynamics model. Â© (2013) Trans Tech Publications, Switzerland.